Bacterial communities in Kuantan estuary of Pahang, Malaysia - Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman; Badrol Hissam, Fairuz Adlinda; John, Akbar; Saad, Shahbudin; Yusof, Faridah (Asian Network for Scientific Information, 2010)
Physicochemical parameters influence the vertical spatial distribution of microbial communities in any water bodies. Based on this perspective, a study on physicochemical parameters and bacterial community was carried out from five stations on January-June 2009 at the Kuantan estuary of Pahang, Malaysia. The temperature was ranged from 25.01-27.48°C, salinity fluctuation observed 0.03-25.84 ppt, Dissolved Oxygen (DO) 6.10 to 10.73 mg L-1, specific conductivity ranged from 0.10 to 42.43 mS cm-1, Total Dissolved Solids (TDS) ranged from 0.05 to 26.36 g L-1) and pH varied from 5.69 to 8.11 and chlorophyll a ranged 0.01 to 1.14 μg L-1. The nitrite concentration was higher at St. 5 (0.19 mg L-1) followed by St. 4 (0.16 mg L-1) and it was lowest at St. 1 (0.13 mg L-1). Similarly, high phosphorus content (0.17 mg L-1) was found at St. 4 followed by St. 5 (0.16 mg L-1) while, it was lowest at St. 1 (0.08 mg L-1). Out of 19 isolated bacteria most dominant bacteria were Citrobacter freundii followed by Leuconostoc sp. and Staphylococcus xylosus. High bacterial colony (cfu mL-1) was observed at St. 4 (570 cfu mL-1) in water column followed by St. 5 (490 cfu mL-1). In contrary, it was lowest at St. 2 (213 cfu mL-1). Meanwhile, the highest bacterial colony in sediment was observed at St. 4 (390 cfu mL-1) followed by St. 5 (333 cfu mL-1). It was lowest observed at St. 2 (167 cfu mL-1). Nevertheless, a continuous monitoring of water quality is needed in this estuary especially at St. 4 and 5 which could be alarming in the long run due to deposition of nutrients from the outlets of fishing villages and industry sources.